Empathy and history : historical understanding in Re-enactment, hermeneutics and education - Retz, Tyson (Making sense of history., 2018)
Since empathy first emerged as an object of inquiry within British history education in the early 1970s, teachers, scholars and policymakers have debated the concept's role in the teaching and learning of history. Yet over the years this discussion has been confined to specialized education outlets, while empathy's broader significance for history and philosophy has too often gone unnoticed.'Empathy and History'is the first comprehensive account of empathy's place in the practice, teaching, and philosophy of history. Beginning with the concept's roots in nineteenth-century German historicism, the book follows its historical development, transformation, and deployment while revealing its relevance for practitioners today.